PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP KREATIVITAS SISWA SMA KELAS XI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA - Intan Ratna Juwita; Andrie Djatmiko, Andreas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of Artificial Intelligence (AI) usage and critical thinking ability on the creativity of eleventh-grade students in Pancasila Education learning at SMA Negeri 1 Kauman. This study employed a quantitative approach with a survey method. The study population consisted of all eleventh-grade students at SMA Negeri 1 Kauman, with a sample of 216 students selected using proportional random sampling technique. The research instrument used was a questionnaire with a 1–5 Likert scale that had been tested for validity and reliability. The data analysis technique used was multiple linear regression analysis. The results showed that: (1) there is a positive and significant effect of AI usage on student creativity, with t-count 2.540 > t-table 1.971 and significance 0.015 < 0.05; (2) there is a positive and significant effect of critical thinking ability on student creativity, with t-count 15.128 > t-table 1.971 and significance 0.000 < 0.05; (3) there is a positive and significant simultaneous effect of AI usage and critical thinking ability on student creativity, with F-count 113.919 > F-table 3.04 and significance 0.000 < 0.05. The coefficient of determination (R²) of 0.517 indicates that both independent variables jointly contribute 51.7% to student creativity. The regression equation obtained is Y = 9.219 + 0.006X₁ + 0.620X₂. Critical thinking ability proved to be a more dominant factor than AI usage in influencing student creativity. All three variables were at a moderate category, meaning they have formed and are running, but are not yet consistent and not yet optimal.